2010
DOI: 10.1038/npp.2010.207
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide S Enhances Memory During the Consolidation Phase and Interacts with Noradrenergic Systems in the Brain

Abstract: Neuropeptide S (NPS) has been shown to promote arousal and anxiolytic-like effects as well as facilitation of fear extinction. In rodents, NPS receptors (NPSR) are prominently expressed in brain structures involved in learning and memory. Here we investigate whether exogenous or endogenous NPS signaling can modulate acquisition, consolidation or recall of emotional, spatial and contextual memory traces, using two common behavioral paradigms, inhibitory avoidance (IA) and novel object recognition. In the IA par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
95
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 47 publications
7
95
0
Order By: Relevance
“…This conclusion is supported by studies showing a lack of phenotype of NPSR(Ϫ/Ϫ) mice in tests for anxiety (elevated plus maze, open field, stress-induced hyperthermia), depressive-like behaviors (forced swimming), memory (novel object recognition), and nociception (formalin) (reviewed by Guerrini et al 2010;Ruzza et al 2012). However, others reported an amnesic (Okamura et al 2011) andanxiogenic-like (Duangdao et al 2009) phenotype for NPSR(Ϫ/Ϫ) mice. Strain differences may explain this discrepancy, suggesting that the endogenous NPS/NPSR system is activated under conditions of high anxiety (i.e., 129S6/SvEv mice and icv injected CD-1 mice) but not low anxiety (i.e., C57BL/6 mice and noninjected CD-1 mice; for discussion see Ruzza et al 2012).…”
Section: Discussionmentioning
confidence: 48%
“…This conclusion is supported by studies showing a lack of phenotype of NPSR(Ϫ/Ϫ) mice in tests for anxiety (elevated plus maze, open field, stress-induced hyperthermia), depressive-like behaviors (forced swimming), memory (novel object recognition), and nociception (formalin) (reviewed by Guerrini et al 2010;Ruzza et al 2012). However, others reported an amnesic (Okamura et al 2011) andanxiogenic-like (Duangdao et al 2009) phenotype for NPSR(Ϫ/Ϫ) mice. Strain differences may explain this discrepancy, suggesting that the endogenous NPS/NPSR system is activated under conditions of high anxiety (i.e., 129S6/SvEv mice and icv injected CD-1 mice) but not low anxiety (i.e., C57BL/6 mice and noninjected CD-1 mice; for discussion see Ruzza et al 2012).…”
Section: Discussionmentioning
confidence: 48%
“…Despite the N-terminal sequence NPS-(1-10) being found to produce a similar maximum effect and potency as the reference peptide NPS- (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) in Roth et al (8), our data showed that NPS-(1-10) was 10-fold less potent as compared with wild type NPS, whereas NPS-(1-13) exhibited similar activities in the stimulation of CRE-driven luciferase activity and Ca 2ϩ mobilization comparable with the full-length NPS peptide. Our observation was consistent with that of Bernier et al (19).…”
Section: Discussionmentioning
confidence: 99%
“…Upon central administration in rodents, NPS has been found to exert a variety of biological effects, including reduction of anxiety-related behavior (1,6,7), increase of locomotor activity (6,8,9), stimulation of wakefulness (1,6), inhibition of food intake (9,10), and enhancement of memory formation (11). Recent studies have also reported its involvement in the suppression of alcohol consumption (12,13) and in the extinction of contextual conditioned fear responses (14,15). Thus, NPS and its cognate receptor represent a novel neurotransmitter system in CNS physiology and pathology and hold great promise for treating a variety of neurological as well as psychiatric conditions.…”
mentioning
confidence: 99%
“…This peptide is also known to influence the HPA axis (Smith et al, 2006), which is involved in the pathogenesis of anxiety and other affective disorders (de Kloet et al, 2005). NPS interacts with many neurotransmitter systems in the brain, including the glutamatergic network (Han et al, 2009;Raiteri et al, 2009;Si et al, 2010;Okamura et al, 2010), which is involved in the pathology of disorders such as PTSD (Rossi et al, 2009;Ravindran and Stein, 2009). The anxiolytic properties of NPS are not mediated by the benzodiazepine-binding site of the GABA A receptor (Leonard et al, 2008), thus suggesting that its administration would not cause benzodiazepine-like side effects.…”
Section: Introductionmentioning
confidence: 99%